Level of adherence to diet and physical activity among menopausal women and influencing factors in Jordan: a descriptive cross-sectional study - Rafi Alnjadat; Eshraq Al Momani; Mohammad Etoom; Falastine Hamdan; Salwa Abu ALrub (Frontiers in Public Health, 2024)
BackgroundDuring menopause, a woman’s lifestyle may change significantly, which will have implications on her quality of life. Women will experience menopause for more than a third of their life; therefore, maintaining good health during this period is crucial. A healthy diet and physical activity can help women maintain their health during menopause. Hence, assessing adherence to a healthy diet and physical activity among menopausal women is important.PurposeThis study aims to assess the degree of adherence to a healthy diet and physical activity of menopausal women in Jordan and determine the most influential factors.MethodsA descriptive cross-sectional design was used in this study, and an online self-administered questionnaire was sent to 299 menopausal women selected through simple random sampling. A valid and reliable questionnaire was used to assess the menopausal women’s adherence to a healthy diet and physical activity. The questionnaire consisted of 14 items covering two domains: 12 questions for the diet domain and two questions for the physical activity domain. Descriptive statistics were obtained, mean weight and body mass index (BMI) were calculated, and stepwise regression was conducted for the data analysis.ResultsThe overall degree of adherence to a healthy diet and physical activity of the women was moderate (49.25, SD = 7.17). Most of the participants reported eating refined food items once a month or less (n = 188, 62.9%) and not exercising weekly (n = 119, 39.8%), and only a few reported eating refined food items at least once a day (n = 5, 1.7%) and exercising 5–6 times a week (n = 15, 5%). The regression analysis showed that age (B = 0.145, p = 0.014), having two children (B = 0.123, p = 0.034) and completing primary or secondary education (B = 0.120, p = 0.038) were statistically significant and the strongest predictors of adherence. The predictors accounted for 68% of the variance in adherence to a healthy diet and physical activity (R2 = 0.068, F [343.54] = 7.123, p = 0.000).ConclusionThe majority of the middle-aged menopausal women in this study showed moderate adherence to a healthy diet and physical activity. Age, having two children and completing primary or secondary education were associated with degree of adherence to a healthy diet and physical activity. Therefore, healthcare intervention, such as physical activity and dietary control programs, should target women in this age group and stage in life.